Optimal Aggressive Constrained Trajectory Synthesis and Control for Multi-Copters - Tsung-Liang Liu; Kamesh Subbarao (Aerospace, 2022)
In this paper, we propose a novel time and control effort optimal aggressive trajectory synthesis and control design methodology. The trajectory synthesis is a modified minimum snap design but with specific position and orientation constraints on a multi-copter, such as flying through tight spaces (windows) at specific orientations. The paper also introduces a means to stitch together multiple flight segments, enforce smoothness, and minimize segment times as well as the overall time, thereby resulting in very aggressive and feasible trajectories. A novel analysis for a specific scenario when no yaw angle specifications are provided is conducted, wherein a trade-off results in additional aggressiveness. The control algorithms to follow these trajectories are based on an inverse dynamics approach. Several candidate high-fidelity simulations are performed to verify the effectiveness of the proposed approach.